2020
DOI: 10.1212/nxi.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte ARNT2 expression is altered in models of MS

Abstract: ObjectiveWe examined expression of aryl hydrocarbon receptor nuclear translocator 2 (ARNT2), a basic-loop-helix transcription factor implicated in neuronal development and axonal health, in oligodendrocyte (OL) cultures and over the course of chronic experimental autoimmune encephalomyelitis (EAE), the murine model of multiple sclerosis (MS).MethodsWe assessed OL ARNT2 expression in EAE compared with sham-immunized controls and also in OL primary cultures and over the course of dibutyryl cyclic adenosine monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Arnt2 expression decreased with the maturation of the OPC cell line Oli-neu. Arnt2 knockdown increased the number of myelinating oligodendrocytes [85].…”
Section: Arnt2mentioning
confidence: 96%
“…Arnt2 expression decreased with the maturation of the OPC cell line Oli-neu. Arnt2 knockdown increased the number of myelinating oligodendrocytes [85].…”
Section: Arnt2mentioning
confidence: 96%
“…OLs are also heterogeneous under pathological conditions. OLs have long been considered as a natural target of MS disease, and studies have shown that human MS and its mouse model EAE have a high degree of OLs diversity (Becquart et al, 2020). Chang et al examined successive white cortical lesions in MS and found that cortical myelin regeneration exceeded WM myelin regeneration in lesions of the same age.…”
Section: The Heterogeneity Of Ols In Physiology and Pathologymentioning
confidence: 99%